Differences in the Use of Euphemisms of Criminality in The Thief and Dogs and Thistle Flowers: A Stylistic Study - Rayhan Hafizh Ananda; Muassomah; Penny Respati Yurisa (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The phenomenon of euphemism often appears in literary works; this element appears to prioritize aesthetic values and taste. Euphemism in literary works is also used as a rhetorical tool that functions to express meanings containing hidden intentions, both implicit and figurative. Therefore, the purpose of this study is to classify the types of euphemisms found in the novels The Thief and The Dogs and Thistle Flowers and to describe the patterns of euphemism in the novels in depicting crime. By using a descriptive qualitative approach with a stylistic analysis method, this study identified 64 euphemistic expressions in the novel The Thief and The Dogs by Najib Mahfouz and the novel Thistle Flowers by Muhammad Farid Abu Hadid, then analyzed using interactive qualitative analysis in the form of data reduction, data presentation and drawing conclusions. Ten types of euphemisms were found in both novels, namely metaphor, understatement, hyperbole, one-to-one substitution, frivolity, general-to-specific, part-to-whole, simile, personification, and irony. The euphemism patterns of these two novels tend to differ in their narratives, which lie in aspects such as theme, euphemistic symbols used, narrative style, and story background. In addition to disguising the implied criminality, euphemism also serves to highlight the emotional side of the characters. This study contributes to Arabic literary stylistics by offering a comparative framework for analyzing euphemism and recommending further research on the role of euphemism in representing social and moral tensions in Arabic narrative fiction. Abstrak Fenomena eufemisme sering muncul dalam karya sastra, unsur ini muncul untuk mengutamakan nilai estetika dan rasa. Eufemisme dalam karya sastra juga digunakan sebagai alat retorika yang berfungsi mengungkapkan makna yang mengandung maksud terselubung, baik implisit maupun figuratif. Maka dari itu, tujuan dari penelitian ini adalah: mengklasifikasikan jenis-jenis eufemisme yang terdapat pada novel The Thief dan The Dogs and Thistle Flowers dan  mendeskripsikan pola eufemisme novel tersebut dalam menggambarkan kriminalitas. Dengan menggunakan pendekatan kualitatif deskriptif dengan metode analisis stilistika, penelitian ini mengidentifikasi 64 ekspresi eufemisme di novel The Thief and The Dogs karya Najib Mahfudz dan novel Thistle Flowers karya Muhammad Farid Abu Hadid kemudian dianalisis dengan analisis kualitatif interaktif berupa reduksi data, penyajian data dan penarikan kesimpulan. Sepuluh jenis eufemisme yang ditemukan dalam kedua novel tersebut, yaitu metafora, pernyataan yang diremehkan, hiperbola, substitusi satu-satu, kesembronoan, umum-ke-khusus, bagian-ke-keseluruhan, simile, personifikasi, dan ironi. Pola eufemisme kedua novel ini cenderung memiliki perbedaan dalam menarasikan eufemisme yang terletak pada aspek-aspek seperti tema, simbol-simbol eufemisme yang digunakan, gaya penuturan, dan latar belakang cerita. Selain untuk menyamarkan makna kriminalitas yang tersirat, eufemisme juga berfungsi untuk menonjolkan sisi emosional tokoh. Penelitian ini berkontribusi pada stilistika sastra Arab dengan menawarkan kerangka komparatif untuk menganalisis eufemisme dan merekomendasikan penelitian lebih lanjut tentang peran eufemisme dalam merepresentasikan ketegangan sosial dan moral dalam fiksi naratif Arab.